Komitmen Politik dan Peluang Pengembangan Kebijakan Gizi Pemerintah Daerah Provinsi Nusa Tenggara Timur - Elisabet Bre Boli; Yayuk Farida Baliwati; Dadang Sukandar (Faculty of Public Health, Hasanuddin University, Makassar, 2018)
East Nusa Tenggara is one of the regions in Indonesia with highest prevalence of malnutrition. Manystudies had identified that political commitment is one of important reason for the low priority of malnutritioninterventions and knowing the policy windows of opportunity could help to advance a new issue and solution. Thisstudy aims to assess political commitment and opportunities to advance nutrition policy reform. This research isa descriptive using primary and secondary data. Primary data collected using PCOM-RAT questionnaire, a rapidassessment tool for identifying political commitment and policy windows of opportunity. The informants were fromNTT Health Office, NTT Development Planning Agency, health academics, and NTT representative of UNICEFwho involved in nutrition policy planning from government and non-government. Data were analyzed descriptivelytoward the result scoring. Results showed that political leaders had verbally and symbolically committedto addressing nutrition problem, but lack of budgetary alocation. Media identified for being incomprehension inreporting nutrition problem without any credible indicators and a well thought-out policy alternative were presentbut still had no feasibility to be implemented.